2015
DOI: 10.1007/s11101-015-9393-5
|View full text |Cite
|
Sign up to set email alerts
|

Solanesol: a review of its resources, derivatives, bioactivities, medicinal applications, and biosynthesis

Abstract: Solanesol, which mainly accumulates in solanaceous crops, including tobacco, tomato, potato, eggplant, and pepper plants, is a long-chain polyisoprenoid alcohol compound with nine isoprene units. Chemical synthesis of solanesol is difficult; therefore, solanesol is primarily extracted from solanaceous crops, particularly tobacco leaves. In plants, solanesol exists in both free and esterified forms, and its accumulation is influenced by genetic and environmental factors. Solanesol is widely used in the pharmace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
77
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 74 publications
(86 reference statements)
9
77
0
2
Order By: Relevance
“…Because the chemical synthesis of solanesol is difficult [11], we assessed some aspects of its biosynthesis in tobacco plants and observed differential accumulation of solanesol in the leaves, stems, and roots of tobacco plants, with the content in leaves being the highest (Figure 2A). Thus, tobacco leaves could be the ideal material for extracting solanesol [3,12]. The results revealed that the solanesol content of leaves varied with growing stage and was highest in leaves from plants in the S3 stage (40 d after transplanting; Figure 2B).…”
Section: Solanesol Is Abundant In Tobacco Leavesmentioning
confidence: 95%
See 3 more Smart Citations
“…Because the chemical synthesis of solanesol is difficult [11], we assessed some aspects of its biosynthesis in tobacco plants and observed differential accumulation of solanesol in the leaves, stems, and roots of tobacco plants, with the content in leaves being the highest (Figure 2A). Thus, tobacco leaves could be the ideal material for extracting solanesol [3,12]. The results revealed that the solanesol content of leaves varied with growing stage and was highest in leaves from plants in the S3 stage (40 d after transplanting; Figure 2B).…”
Section: Solanesol Is Abundant In Tobacco Leavesmentioning
confidence: 95%
“…Solanesol is a long-chain polyisoprenoid alcohol that mainly accumulates in solanaceous plants, especially tobacco [1,3,12], and is an important intermediate in the synthesis of ubiquinones and anticancer drugs. Because the chemical synthesis of solanesol is difficult [11], we assessed some aspects of its biosynthesis in tobacco plants and observed differential accumulation of solanesol in the leaves, stems, and roots of tobacco plants, with the content in leaves being the highest (Figure 2A).…”
Section: Solanesol Is Abundant In Tobacco Leavesmentioning
confidence: 99%
See 2 more Smart Citations
“…Yan et al (2015) summarized the resource, derivatives, bioactivities, and medicinal applications of solanesol. Solanesol was widely used as an intermediate for the synthesis of ubiquinone drugs, such as coenzyme Q10 and vitamin K2.…”
mentioning
confidence: 99%